(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article highlights the modern directions of pedagogy and the significance of innovative teaching methods. The use of interactive techniques, information and communication technologies, and creative approaches enhances students’ knowledge, skills, and abilities. Innovative methods not only improve the quality of education but also foster personal and social competencies. The findings demonstrate the effectiveness of integrating advanced approaches into the educational process.